Approaches to Assure Similarity between Pharmaceutical Heparins from Two Different Manufacturers - Francisco Felipe Bezerra; Stephan N.M.C.G. Oliveira; Rodrigo A. Sales; Adriana A. Piquet; Nina V. Capillé; Eduardo Vilanova; Ana M.F. Tovar; Paulo A.S. Mourão (MDPI AG, 2023)
Pharmaceutical heparins from different manufacturers may present heterogeneities due to particular extraction and purification procedures or even variations in the raw material manipulation. Heparins obtained from different tissues also differ in their structure and activity. Nevertheless, there is an increased demand for more accurate assessments to ensure the similarities of pharmaceutical heparins. We propose an approach to accurately assess the similarity of these pharmaceutical preparations based on well-defined criteria, which are verified with a variety of refined analytical methods. We evaluate six commercial batches from two different manufacturers which were formulated with Brazilian or Chinese active pharmaceutical ingredients. Biochemical and spectroscopic methods and analysis based on digestion with heparinases were employed to evaluate the purity and structure of the heparins. Specific assays were employed to evaluate the biological activity. We observed minor but significant differences between the constitutive units of the heparins from these two manufacturers, such as the content of N-acetylated α-glucosamine. They also have minor differences in their molecular masses. These physicochemical differences have no impact on the anticoagulant activity but can indicate particularities on their manufacturing processes. The protocol we propose here for analyzing the similarity of unfractionated heparins is analogous to those successfully employed to compare low-molecular-weight heparins.